Antiseptic Skin Preparation Agents to Prevent Surgical Site Infection in Colorectal Surgery: A 3-Armed Randomized Controlled Trial. Issue 11 (20th December 2021) - Reid, Fiona S.; Stephensen, Bree; Carroll, Rosemary; Lott, Natalie; Attia, John R.; Smith, Stephen R.
Abstract : BACKGROUND: There is much debate surrounding the ideal antiseptic skin preparation agent to reduce postoperative surgical site infection. International guidelines suggest that chlorhexidine- and alcohol-containing compounds have superior efficacy. However, there are minimal clinical trials specifically looking at skin preparation agents for colorectal surgery. OBJECTIVE: The aim of this study was to compare the efficacy of chlorhexidine in alcohol versus povidone-iodine in alcohol versus povidone-iodine in aqueous solution for the prevention of surgical site infection in colorectal surgery. DESIGN: This is a prospective, 3-armed, randomized controlled trial. SETTING: This study was conducted at the 800-bed John Hunter Hospital and Newcastle Private Hospital, with all subspecialty services in New South Wales, Australia. PATIENTS: All eligible, consenting adults undergoing colorectal surgery between July 2015 and December 2018 were included. INTERVENTIONS: Patients were andomized to receive preincision skin preparation with one of the following: chlorhexidine in 70% alcohol, povidone-iodine in 70% alcohol, or povidone-iodine in aqueous solution. MAIN OUTCOME MEASURE : The primary measure was surgical site infection within 30 days. RESULTS: A total of 482 patients were randomized to chlorhexidine in alcohol, povidone-iodine in alcohol, or aqueous povidone-iodine. The overall surgical site infection rate was 22% (107/482). There was no difference in rates of surgical site infection: 20.6% (29/141), 22.8% (44/193), and 23.0% (34/148), respectively ( p = 0.5267). There was no difference in complication rates: 54.6% (77/141), 46.1% (89/193), and 49.3% (73/148), respectively ( p = 0.1762). The median length of stay was 6 days in all 3 groups. LIMITATIONS: This is a subset analysis of a larger clinical trial for all forms of incisional surgery (the NewSKIN Prep trial), and noninferiority cannot be assessed. Changes in government regulations resulted in a change from 0.5% chlorhexidine in 70% ethanol to 2% chlorhexidine in 70% ethanol during the trial. CONCLUSION: This large, prospective, randomized clinical trial appears to indicate that there is no difference in surgical site infection, complications, or length of stay among the 3 commonest forms of skin preparation in colorectal surgery. See Video Abstract at http://links.lww.com/DCR/B875 . New Zealand Clinical Trials registry: ACTRN12615000021572 Agentes antisépticos para la preparación de la piel para prevenir la infección del sitio quirúrgico en la cirugía colorrectal: un ensayo clínico aleatorizado de tres grupos ANTECEDENTES: Existe un gran debate en torno al agente de preparación de la piel antiséptico ideal para reducir la infección posoperatoria del sitio quirúrgico. Las pautas internacionales sugieren que los compuestos que contienen clorhexidina y alcohol tienen una eficacia. Sin embargo, existen ensayos clínicos mínimos que analizan específicamente los agentes de preparación de la piel para la cirugía colorrectal. OBJETIVO: Comparar la eficacia de la clorhexidina en alcohol versus povidona yodada en alcohol versus povidona yodada en solución acuosa para la prevención de la infección del sitio quirúrgico en cirugía colorrectal. DISEÑO: Este es un ensayo controlado aleatorio prospectivo de tres brazos. AJUSTE: Este estudio se realizó en el Hospital John Hunter de 800 camas y el Hospital Privado de Newcastle con todos los servicios de subespecialidad en Nueva Gales del Sur, Australia. PACIENTES: Se incluyeron todos los adultos elegibles que dieron su consentimiento para someterse a una cirugía colorrectal entre julio de 2015 y diciembre de 2018. INTERVENCIONES: Aleatorizados para recibir una preparación para la piel previa a la incisión con uno de: clorhexidina en alcohol al 70%, povidona yodada en alcohol al 70% o povidona yodada en solución acuosa. MEDIDA DE RESULTADO PRINCIPAL: La medida principal fue la infección del sitio quirúrgico dentro de los 30 días. RESULTADOS: Un total de 482 pacientes fueron aleatorizados para recibir clorhexidina en alcohol, povidona yodada en alcohol o povidona yodada acuosa. La tasa global de infección del sitio quirúrgico fue del 22% (107/482). No hubo diferencias en las tasas de infección del sitio quirúrgico; 20, 6% (29/141), 22, 8% (44/193) y 23, 0% (34/148) respectivamente; p = 0, 5267. No hubo diferencia en las tasas de complicaciones; 54, 6% (77/141), 46, 1% (89/193) y 49, 3% (73/148) respectivamente; p = 0, 1762. La duración media de la estancia hospitalaria fue de 6, 0 días en los tres grupos. LIMITACIONES: Este es un análisis de subconjunto de un ensayo clínico más grande para todas las formas de cirugía incisional (el ensayo NewSKIN Prep) y no se puede evaluar la no inferioridad. Los cambios en las regulaciones gubernamentales dieron como resultado un cambio de clorhexidina al 0, 5% en etanol al 70% a clorhexidina al 2% en etanol al 70% durante la prueba. CONCLUSIÓNES: Este gran ensayo clínico prospectivo y aleatorizado parece indicar que no hay diferencia en la infección del sitio quirúrgico, las complicaciones o la duración de la estancia entre las 3 formas más comunes de preparación de la piel en la cirugía colorrectal. Consulte Video Resumen en http://links.lww.com/DCR/B875 . (Traducción—Dr. Gonzalo Hagerman ) Este ensayo se registró de forma prospectiva en el registro de ensayos clínicos de Australia Nueva Zelanda el 15/01/2015: ACTRN12615000021572